Experimental Programs of Critical Thinking Enhancement: A Worked-Based, Blended Learning Higher Education Curriculum for Economics - Daniela Dumitru; Mihaela Minciu; Robert Alexandru Mihaila; Raluca Livinti; Monica Elisabeta Paduraru (MDPI AG, 2023)
In an increasingly changing world, critical thinking is one of the key skills that ensure organizations' competitive advantage. Thus, in higher education institutions, there is an accelerating emphasis on developing critical thinking (CT) among students. This paper presented the results of three experimental courses (pedagogy and didactics of financial accounting, virtual learning environments in economics, and business communication), using a blended learning method, aimed at improving students' CT skills. The three courses were delivered by both higher education teachers and trainers from the labor market. After analyzing the data from the three experimental courses, it will be possible to assess whether the intervention of labor market trainers contributed to the improvement of students' critical thinking skills, and in particular, at the level of which these component improvements have been identified.